If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(13x+4)(10x-1)=141
We move all terms to the left:
(13x+4)(10x-1)-(141)=0
We multiply parentheses ..
(+130x^2-13x+40x-4)-141=0
We get rid of parentheses
130x^2-13x+40x-4-141=0
We add all the numbers together, and all the variables
130x^2+27x-145=0
a = 130; b = 27; c = -145;
Δ = b2-4ac
Δ = 272-4·130·(-145)
Δ = 76129
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(27)-\sqrt{76129}}{2*130}=\frac{-27-\sqrt{76129}}{260} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(27)+\sqrt{76129}}{2*130}=\frac{-27+\sqrt{76129}}{260} $
| e+12=16 | | 2s+6=-3+3s | | y(20+16.84)=92.1 | | 20=-20r | | h3+-7=-10 | | -5x+2x-1=-3x-2 | | −3x+8x+10=−20 | | b-7.1-2=-3.3 | | x7+6=14 | | 6=(4x÷45)÷x | | O=-4p+4p | | 6=(4x/45)÷x | | 2.3x+5.4=10 | | 3x–3=5x+6–2x | | 10=12-4(x+2)+2x | | 2.77(s-7)-1.7=3.84 | | 6x^2(x+2)+24x^2(x+48x(x=0 | | 2h=10+8(h+4) | | -100=-40+10x | | 8y-8=120 | | x+.3x=128140 | | 3c−1c=4 | | -10q+3=7-9q | | 7x-35+x+4+4x-8=180 | | 22n=8n+98 | | 6j-10=-2-2j+4 | | -3-2x+8=5-2x | | 18y+46=172 | | -1+5(-3p+8)=-8(p+3) | | 2.7x=4.475x | | d/6d=30 | | (1)/(3)x+11=8 |